Pregnancy outcomes of normal versus abnormal cardiotocography in a tertiary centre in Nepal - Faruqi, Mariyam; Shrestha, Shailaja C.; Bhatta, Rabindra D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy and childbirth is normal physiological process with great pathological potential. The obstetricians are more concerned with the early recognition of fetal distress during labour and such an adverse outcome should be detected at the earliest point of time by an effective surveillance method. Cardiotocography as a part of biophysical profile has become an established diagnostic tool for fetal surveillance. To compare early perinatal outcome of normal and abnormal cardiotocography in terms of APGAR scores, need for neonatal resuscitation, NICU admission, perinatal death and mode of delivery. Methods: It was a cross-sectional study. 200 nulliparous/multiparous women with singleton pregnancy in cephalic presentation at gestational age 37-42 weeks in latent stage of labor were enrolled in the study and subjected to admission test in left lateral position using fetal monitor. Baseline FHR and contraction pattern were determined for 20 minutes and classification of patients was done into normal, and suspicious or abnormal according to the FIGO guidelines 2015. Results: Low APGAR scores, rate of LSCS, need for neonatal resuscitation, neonatal admission were more in the abnormal cardiotocography group. Cardiotocography in the current study has high sensitivity and high negative predictive value for detecting fetal distress. Conclusions: From the analysis of this study, it would be safe to conclude that an ominous cardiotocography should be managed appropriately without delay and obstetrician should be vigilant in suspicious as well as in normal admission test group for timely intervention for bettering the neonatal outcome.